1972
DOI: 10.1136/gut.13.11.887
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gastrin and acid secretion in man following stimulation by food, meat extract, and insulin

Abstract: SUMMARY A radioimmunoassay for gastrin was set up and its sensitivity and specificity were studied. The assay was then used to investigate the plasma gastrin responses in man to a normal meal and to stimulation by insulin hypoglycaemia or by instilling meat extract into the stomach. The results showed that insulin and meat extract produced very similar plasma gastrin responses which were certainly not less than those produced by feeding. However, the acid secretory response to insulin was greater than that to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…There can be no doubt that the vagus nerve will release gastrin under physiological circumstances in man (Knutson et al, 1974); equally there can be no doubt that even after division of the vagus nerve gastrin can be released by physiological stimuli, such as food . Presuming that our findings and those of other groups already mentioned (Ganguli and Elder, 1971; Wyllie et al, 1972;Stadil, 1974) are true, then it is necessary to explain the rise in gastrin during insulin hypoglycaemia in the absence of vagal excitation of gastric acid. Possible explanations include: first, that although vagotomy is complete with regard to the parietal cells there are still vagal fibres which innervate the gastrin G-cells in the stomach or duodenum; secondly, that insulin hypoglycaemia stimulates the sympathetic nervous system which, in turn, stimulates the release of gastrin (Stadil and Rehfeld, 1973); thirdly, that hypoglycaemia has an effect on the release of gastrin, either directly on the gastrin G-cell or via another intermediary.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There can be no doubt that the vagus nerve will release gastrin under physiological circumstances in man (Knutson et al, 1974); equally there can be no doubt that even after division of the vagus nerve gastrin can be released by physiological stimuli, such as food . Presuming that our findings and those of other groups already mentioned (Ganguli and Elder, 1971; Wyllie et al, 1972;Stadil, 1974) are true, then it is necessary to explain the rise in gastrin during insulin hypoglycaemia in the absence of vagal excitation of gastric acid. Possible explanations include: first, that although vagotomy is complete with regard to the parietal cells there are still vagal fibres which innervate the gastrin G-cells in the stomach or duodenum; secondly, that insulin hypoglycaemia stimulates the sympathetic nervous system which, in turn, stimulates the release of gastrin (Stadil and Rehfeld, 1973); thirdly, that hypoglycaemia has an effect on the release of gastrin, either directly on the gastrin G-cell or via another intermediary.…”
Section: Discussionmentioning
confidence: 58%
“…None the less, this problem remains controversial. For example, abolition of gastrin response has been reported after vagotomy Cowley et al, 1973;Korman et al, 1973), whereas persistence of this response has been found by other groups (Ganguli and Elder, 1971 ;Wyllie et al, 1972;Jaffe et al, 1974;Stadil, 1974). There are two important reasons why this discrepancy should be resolved : first, to elucidate the physiological mechanisms involved, and secondly, because the measurement of plasma gastrin concentration following insulin hypoglycaemia might offer a more convenient index of completeness of vagotomy than gastric secretion, provided that vagal innervation of the G-cells is necessary for the gastrin response.…”
mentioning
confidence: 90%
“…Acute neutralization of the stomach by instillation of bicarbonate enhances the gastrin response after stimulation with insulin, 2-deoxy-rf-glucose, C 0 2 rebreathing and a test meal (14,17). Prolonged achlorhydria is associated with an increased number of antral G cells, resulting not only in an elevated fasting gastrin con centration, but also in an increased gastrin response to different stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin hypoglycemia is known to cause the release of gastrin in dogs (Kemp et al, 1968;Jaffe et al, 1970) and man (Wyllie et al, 1972;Hansky et al, 1972;Hodge et al, 1972;Stadil and Rehfeld, 1972;Cowley and Baron, 1973). The mechanism of gastrin release by insulin hypoglycemia, however, is not understood.…”
Section: Synopsismentioning
confidence: 99%